Design and development of multi-lane smart electromechanical actuators - Annaz, Fawaz Yahya (The Institution of Engineering and Technology, 2013)
Design and Development of Multi-Lane Smart Electromechanical Actuators presents the design of electromechanical actuators in two types of architectures, namely, Torque Summed Architecture (TSA) and Velocity Summed Architecture, (VSA). It examines them in: * Hardware redundancy, where the architecture is made up of 3 or 4 lanes. * Digital Math Model redundancy, where a more compact two lanes architectures will be presented.
Keywords: Actuators.; Control theory.; elektronické knihy; electronic books